(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Income Comparison of Rice Plants (Oryza sativa L.) with water ehnna (Impatiens balsamina L.) Farming in Lodtunduh Subak, Gianyar Regency. Rice and water henna flower farming in Subak Lodtunduh is a continuous activity that can be carried out simultaneously because, in Subak Lodtunduh, water is relatively always sufficient throughout the year. The purpose of this study was to determine the income, income differences, and feasibility of rice farming and water henna flower in Subak Lodtunduh. Quantitative data in this study include the amount of production and selling prices at the producer level. Qualitative data in this study include a description of the area studied and an overview of Subak Lodtunduh. The population in this study was 32 Subak Lodtunduh farmers. The population of farmers who only grow rice is 16 people. The population of farmers who grow water henna flowers is as large as 16 people. Samples taken by census of the total population The average income of rice farming in one growing season is Rp. 15,389,092.78/ha, while the average income of water henna flower farming in two growing seasons is Rp. 38,402,163.63/ha. A comparison of rice farming income with water henna flowers in Subak Lodtunduh shows a significant difference because it has a sig value of 0.05. Rice farming and water henna flower cultivation in Subak Lodtunduh are declared feasible to cultivate because they have an R/C ratio value> 1 and a B/C ratio value> 0. The suggestions given are that, with the large labor costs in water henna flower farming, farmers are advised to cultivate rice unless there is sufficient labor availability in water henna flower farmer households. Because the absorption of labor for water henna flower farming is very high, as evidenced by the relatively high labor costs of other costs.